Evolution of galaxy size–stellar mass relation from the Kilo-Degree Survey. Issue 1 (19th July 2018) - Roy, N; Napolitano, N R; Barbera, F La; Tortora, C; Getman, F; Radovich, M; Capaccioli, M; Brescia, M; Cavuoti, S; Longo, G; Raj, M A; Puddu, E; et al.
ABSTRACT: We have obtained structural parameters of about 340 000 galaxies from the Kilo-Degree Survey (KiDS) in 153 deg 2 of data release 1, 2, and 3. We have performed a seeing convolved 2D single Sérsic fit to the galaxy images in the four photometric bands ( u, g, r, i ) observed by KiDS, by selecting high signal-to-noise ratio (S/N > 50) systems in every bands. We have classified galaxies as spheroids and disc-dominated by combining their spectral energy distribution properties and their Sérsic index. Using photometric redshifts derived from a machine learning technique, we have determined the evolution of the effective radius, R e and stellar mass, M ⋆, versus redshift, for both mass complete samples of spheroids and disc-dominated galaxies up to z ∼0.6. Our results show a significant evolution of the structural quantities at intermediate redshift for the massive spheroids (log M * /M⊙ > 11, Chabrier IMF), while almost no evolution has found for less massive ones (log M * /M⊙ < 11). On the other hand, disc dominated systems show a milder evolution in the less massive systems (log M * /M⊙ < 11) and possibly no evolution of the more massive systems. These trends are generally consistent with predictions from hydrodynamical simulations and independent datasets out to redshift z ∼ 0.6, although in some cases the scatter of the data is large to drive final conclusions. These results, based on 1/10 of the expected KiDS area, reinforce precedent finding based on smaller statistical samples and show the route towards more accurate results, expected with the the next survey releases.